Functional responsibility: lessons from genocide - Muhammad Zulkhairi Bin Hamdan (Nanyang Technological University, 2025)
Attributing responsibilities to harm done is critical in moral ascriptions and legal proceedings. This is especially crucial in large-scale harms such as the Israeli-Gaza Genocide. A clear and blatant violation of humanity requires strict punishment in order to appropriately hold the right parties responsible. ‘Responsibility’, however, is a term that is taken lightly. Reductionists and Collectivists put forward their ideas and assertions of what responsibility entails and who can be held responsible for harms done. But the debate operates on a shallow understanding of ‘responsibility’ as if it were an intrinsic property that has a meaning by virtue of its own self. In this paper, I put forward a clearer outline of the roles and functions that ‘responsibility’ plays, and the functional and adaptive nature of the concept. The paper will explore our use of the term ‘responsibility’ in order to flesh out how it carries a number of different meaning and functions in different contexts. This functional framework then is applied to the case study of the Israeli-Gaza Genocide in order to demonstrate that its use covers the holes and gaps left behind by the inadequacies of the reductionist and collectivist approach.